Effect Of Crude Aldehyde Dehydrogenase On The Degradation Of Crude Oil By A Local Isolate, Acinetobacter Baumannii Fetl C4 - Chee , Mei Sing (2010)

(untitled)
Detection of hydrocarbon-degrading enzymes activities in microorganisms capable of utilizing crude oil as a carbon source were done using potential oil-degraders isolated from soil and water samples collected from water and oil-contaminated areas in Penang. Seven potential isolates categorized as Group I bacteria were selected based on the criteria that they displayed good growth on solid crude oil medium using 6 different types of crude oil which were named as. Tapis, Khefji Dubai, Bunga Kekwa, Angsi, Dulang, and Penara. These crude oil media were prepared without the addition of surfactant. Out of seven isolates, oil-degrading bacterium designated as FETL C4 displayed good growth on different types of crude oil media prepared. Biochemical test results identified this isolate as Acinetobacter sp. Further confirmation was done using 16S rRNA gene analysis and Remel Rapid Identification Kit. Aldehyde dehydrogenase (ALDH) activity was detected during the cultivation of this isolate when grown in minimal salt medium containing 1% (w/v) Tapis crude as a carbon source. Optimizations on the production of this enzyme were done by manipulating physical and chemical parameters of the growth and enzyme production. The optimization process were carried out in a flask system (250 mL) and then further scaled up via fermenter system (5 L). Cells were harvested from the growth medium when maximum points were reached for both enzyme activity and degradation of the crude oil. The optimal conditions when aldehyde dehydrogenase activity detected at the highest rate were obtained at 0.2 giL (NH4)2S04, 0.4 giL KH2P04, 0.8 giL Na2HP04, 1.0 giL Tapis crude, 0.2 giL Tween 80 as surfactant, cultivation temperature at 37°C, initial medium pH 8.0, with addition of 5% inoculum (1 x 106 cells/mL) and agitated at 600 rpm. Aeration rate was set at 2L per minute to enhance the growth of the isolate. Biomass production and degradation rate of the crude oil were 2.0 giL and 70%, respectively. Zymogram analysis of aldehyde dehydrogenase on different aldehyde substrates revealed that only one activity band that involved in the metabolism of various aldehyde substrates. Quantitative analysis of this enzyme on different aldehyde substrates showed a higher preference towards aldehyde with carbon 12.